Course of cognitive impairment following attempted suicide in older adults. (21st October 2015) - Gujral, Swathi; Ogbagaber, Semhar; Dombrovski, Alexandre Y.; Butters, Meryl A.; Karp, Jordan F.; Szanto, Katalin
Abstract : Objective: Cognitive impairment has been associated with late‐life suicidal behavior. Without longitudinal data it is unclear whether these are transient features of a depressive state or stable impairments. We examined longitudinally the course of cognitive impairment in older adults with depression and a history of suicide attempt. Methods: We investigated the persistence of cognitive impairment over time in 198 depressed older adults (age >60); 91 suicide attempters, 39 depressed individuals with suicidal ideation (ideators), and 68 non‐suicidal depressed adults assessed over a 2‐year period at four time points. We used linear mixed effects modeling to examine group differences in trajectories of cognitive decline over 2 years, using the Mini‐Mental State Examination (MMSE), Mattis Dementia Rating Scale (DRS), and Executive Interview (EXIT). Results: Over the 2‐year period, suicide attempters performed significantly worse than both suicide ideators and non‐suicidal depressed older adults on the MMSE (mean difference: from ideators: −0.88, p  = 0.02; from non‐suicidal depressed: −1.52, p  < 0.01), while on the EXIT and DRS, suicide attempters performed significantly worse than non‐suicidal depressed older adults (mean difference: in EXIT: −1.75, p  = 0.01; in DRS: 3.04, p  < 0.01; in MMSE: 1.15, p  < 0.01). Cognitive impairment in suicide attempters partly resolved, as indicated by a group × time interaction on the DRS ( p  = 0.039), but not the EXIT ( p  = 0.58) or the MMSE ( p  = 0.08). Conclusions: Cognitive impairment in late‐life suicidal behavior appears to involve both a stable and a state‐related component. Copyright © 2015 John Wiley & Sons, Ltd.